The Wandering Rash..... An unusual case of Benign Migratory Glossitis that healed with anti fungal treatment - Freny Karjodkar; Antara Sinha (Wolters Kluwer Medknow Publications, 2004)
Benign migratory glossitis, also named as Geographic tongue, Wandering rash of tongue, Glossitis Areata Exfoliativa, Erythema migrans is a lesion of unknown etiology and is usually asymptomatic.